Thank you, Amelia Bedelia - Parish, Peggy; Siebel, Fritz (New York : HarperCollinsPublishers, 1993)
Preparing for the arrival of an important visitor, a wacky housekeeper follows her employer's instructions with humorous results.
Keywords: Household employees -- Fiction; Humorous Stories